PERAN BANTUAN LANGSUNG TUNAI DANA DESA (BLT-DD) DALAM UPAYA MENINGKATKAN DAYA BELI MASYARAKAT DESA MATANG LABONG MENURUT PERSPEKTIK EKONOMI ISLAM - Santi; Wahab; maskupah (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2026)
This research uses a qualitative approach and the type of research used is descriptive. The place that is the object of this research is Mature Labong village. The data sources used are primary data and secondary data. Data collection in this research used observation, interview and documentation methods. The analytical method used is a qualitative analysis method. Direct cash assistance from village funds is very good for the community, where this assistance can help the economy of the poor, the distribution of this assistance also meets the specified criteria, such as people who have illnesses and people who have given up their businesses so they have no income. The form of cash is given to prevent the decline in purchasing power of poor people caused by rising prices of basic commodities.